Strategic Goals of Financial Management of Hangzhou Yateyuan Technology Co., Ltd. in The International Market - Zhecui Wei; Maxim Vasilyevich Chernyaev (Communications of International Proceedings, 2022)
Finance is critical to the success of all companies. Financial management of an enterprise is one of the most important tasks facing any business, regardless of the scope and scale of its activities. The importance of this area is due to the special role of finance, which is the only type of resources that can be transformed into any other type of resources - tangible and intangible assets. The efficiency and rationality of such a transformation largely determines the economic well-being of the company, as well as all subjects interested in its development, namely: shareholders, managers, creditors, the state, society. Thus, the management of financial resources in the international market is necessary for any company. The main point of managing financial resources is to get the maximum result at a minimum cost, that is, to earn the largest amount of money. Therefore, applying methods of operational financial management, companies strive to ensure stable and predictable development, enable their divisions to effectively perform the functions assigned to them, have a backup scenario and room for maneuver in a changing external environment, in order to ultimately become the most stable from a financial point of view. view of the business unit.
Keywords: financial management; financial resources; company strategy; international market; economic efficiency.